Low-carbon land transport : policy handbook - Bongardt, Daniel (New York : Routledge, 2013)
This book provides a guide for transport policymakers and planners on achieving low-carbon land transport systems and describes possible measures for reducing emissions. Based on wide ranging research, case studies from developed and developing countries and an overview of policy scenarios, the book presents a toolbox for decision-makers with a huge variety of measures which can be tailored to their specific circumstances. It also addresses the question of how policies can be bundled successfully and integrated in urban transport decision-making and planning. Practical information is given on how greenhouse gas savings are measured as well as details of international support structures--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Greenhouse gas mitigation -- Government policy; Transportation, Automotive -- Environmental aspects; Sustainable urban development -- Government policy; Carbon dioxide mitigation; Transportation and state; Electronic books